Desenvolvimento de nanocápsulas contendo cetoprofeno e avaliação in vitro da citotoxicidade - Ribas, Daniele Adriane (2013)
The aim of this work was to prepare, characterize and evaluate the in vitro cytotoxicity of Eudragit S100® nanocapsules (NC) containing ketoprofen. The nanostructured suspensions were prepared in triplicate by the method of interfacial deposition of preformed polymer. Caprilic/capric triglyceride or rosehip oil were used as the oil core in the preparation of such formulations. Previously, tests of swelling/dissolution of the films of Eudragit S100® were performed and showed the feasibility of using both oils as the core of the NC. The results of the physico-chemical characterization of the systems (pH, size, zeta potential, content, encapsulation efficiency) showed no significant differences between the various types of formulations. The concentration of ketoprofen in the formulations was very close to the theoretical concentration, indicating no loss or degradation of the drug during the preparation process. The encapsulation efficiency of ketoprofen in NC was higher than 90%. The particle size of the formulations was found in the range of 173-197 nm, which is in accordance to the method of preparation employed. Regarding the in vitro release, the mathematical analysis of the profiles showed a first order kinetics with drug diffusion as release mechanism. In order to evaluate the influence of the oil component in the ketoprofen photodegradation, samples were exposed to UVC radiation. The photodegradation was less evident in the rosehip oil NC, probably due to the greatest antioxidant potential of this oil. The in vitro cytotoxicity assay evaluated the viability of 3T3 cell line against four concentrations of ketoprofen (1, 10, 50 and 100 μM) for 24 and 48 hours. After 48 hours of exposure, there was a reduction in cell viability in all tested groups. However, this decrease was not significantly different from the control group. Thus, the prepared formulations can be considered promising alternatives for the delivery of ketoprofen in inflammatory diseases such as rheumatoid arthritis.